The Analysis of Implementation of Specific and Sensitive Nutritional Intervention Programs in Reducing Stunting Toddler in Langkat District 2018 - Purba, Risma Oktoria; Siagian, Albiner; Aulia, Destanul (Budapest International Research and Critics University, 2020)
There are five districts with the highest stunting rate in North Sumatra and in Langkat district by 38.7 percent in 2017. This research looks at the analysis of the implementation of specific and sensitive nutrition intervention programs to reduce stunting rates in langkat. This research is a qualitative study with a phenomological design using purposive sampling method with 8 informants with the criteria of program implementers and field implementers and the community using CFIR tools to see the implementation of specific and sensitive nutrition intervention programs to reduce stunting in toddlers in Langkat. From the analysis of 31 CFIR constructs, there are 6 strong constructs of influence, where 4 constructs have a positive effect, namely the characteristics of the agency structure, pressure to change, self-confidence, program adoption and 2 constructs have a negative effect, namely external networks and external needs and incentives. There are 4 constructs that have a weak but very impactful effect where 3 constructs have a negative effect, namely the impact and desired change, the involvement of the leader and available resources and 1 construction has a positive effect, namely the level of individual change on the reduction of stunting rates in children under five in Langkat. However, improvements are needed in terms of cooperation between agencies, budgeting, additional special programs outside the specific and sensitive nutrition intervention program, the appointment of a special program leader and support for facilities, infrastructure and human resources for the implementation of the specific and sensitive nutrition intervention program in Langkat district.